2008
DOI: 10.1097/01.ogx.0000300424.58703.1f
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Gestational Diabetes in Women Receiving Prophylactic 17α-Hydroxyprogesterone Caproate for Prevention of Recurrent Preterm Delivery

Abstract: A recent study showed that 5% of pregnant white women and 29% of pregnant blacks in the northeastern United States had vitamin D deficiency, defined as a serum level of 25-hydroxyvitamin D [25(OH)D] less than 37.5 nmol/liter. About half of women in both groups had evidence of vitamin D insufficiency, with 25(OH)D levels of 37.5-80 nmol/liter. These findings are ascribed both to a lack of adequate solar exposure and a low oral intake of vitamin D even when a 400-IU supplement is taken. The racial disparity in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Exogenous progesterone decreases insulin sensitivity with the subsequent development of hyperglycemia in rodents (14,20), and the use of 17-OHPC to prevent recurrent preterm delivery is associated with an increased risk of developing glucose intolerance and gestational diabetes mellitus in humans (16,17). In addition, the levels of homeosta-sis model of insulin resistance (HOMA-IR) increase during the luteal phase of the menstrual cycle in association with increases in the serum progesterone levels in humans (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous progesterone decreases insulin sensitivity with the subsequent development of hyperglycemia in rodents (14,20), and the use of 17-OHPC to prevent recurrent preterm delivery is associated with an increased risk of developing glucose intolerance and gestational diabetes mellitus in humans (16,17). In addition, the levels of homeosta-sis model of insulin resistance (HOMA-IR) increase during the luteal phase of the menstrual cycle in association with increases in the serum progesterone levels in humans (23).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a correlation between high progesterone levels and glucose intolerance (14,(16)(17)(18)(19)(20)(21)(22)(23). Exogenous progesterone decreases insulin sensitivity with the subsequent development of hyperglycemia in rodents (14,20), and the use of 17-OHPC to prevent recurrent preterm delivery is associated with an increased risk of developing glucose intolerance and gestational diabetes mellitus in humans (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Side effects reported in the literature include pain, swelling, pruritis and nodule formation at the injection site, urticaria, nausea and vomiting, mood swings, bloating, abdominal pain, depression, nervousness, sleep disorder and tiredness, dizziness, fever, flu-like symptoms, upper respiratory infection, urinary tract infection, yeast infection, asthma, acne and pain in the joints, back and leg [29,52]. Weekly 17 OHP-C prophylaxis has also been linked with an increased risk of gestational diabetes mellitus in women with a history of spontaneous preterm birth (odds ratio 2.9, 95% CI 2.1-4.1) [53].…”
Section: Safetymentioning
confidence: 98%
“…Although there were no differences in the treatment compliance rate between the three groups studied, a small percentage of women in each group did not complete the study (P = NS). The side effects of progestogens are poorly reported, except that intramuscular 17P appears to raise the risk for gestational diabetes, 20 and oral natural progesterone, given in very high doses (600-1200 mg/day), may induce liver dysfunction. 21,22 In our trial, no serious systemic adverse effects were encountered, the local tolerance was good in all but one woman and the rate of gestational problems was not higher in progesterone-treated women, except for Results expressed as means ± standard deviations or n (%).…”
mentioning
confidence: 99%